Cis‐On/trans‐Off of DNA Hybridization with Alkylthio‐azobenzene on L‐Threoninol Responding to Visible Light. Issue 6 (22nd May 2019) - Asanuma, Hiroyuki; Ishikawa, Teruchika; Yamano, Yuuhei; Murayama, Keiji; Liang, Xingguo
Abstract: An azobenzene modified with a highly branched secondary alkylthio group incorporated into DNA via an L‐threoninol scaffold can serve as a photo‐switch to reversibly control DNA hybridization. In the system reported here, irradiation with visible light at 400 nm causes photo‐isomerization of trans ‐azobenzene to cis and 520 nm light causes the switch to the trans form. The DNA duplex is formed when the azobenzene is in the cis form (upon irradiation with 400 nm light) and is dissociated when the azobenzene is in the trans form (upon irradiation with 520 nm light). In our previously reported system, the switch required UV light. Here, visible light was used to induce both isomerizations, and a smooth trans ‐to‐ cis isomerization was observed below the melting temperature. This new photo‐switch with visible light overcomes one of the limitations for the potential in vivo use of our method. Combining it with the previously reported photo‐switch will allow the construction of elaborate DNA nanomachines. Abstract : An azobenzene modified with a highly branched secondary alkylthio group incorporated into DNA via an l ‐threoninol scaffold can serve as a photo‐switch to reversibly control DNA hybridization. The DNA duplex adopts the cis form upon irradiation with 400 nm light and is dissociated into the trans form when 520 nm light is used.